2017
DOI: 10.1177/1932202x17738989
|View full text |Cite
|
Sign up to set email alerts
|

Determining Attitudes Toward Ability: A New Tool for New Understanding

Abstract: The purpose of this study is to explore teacher attitudes toward gifted students in several distinct areas and to provide psychometric evidence of reliability and validity for the use of an instrument titled "Determining Attitudes Toward Ability" (DATA) to measure specific components of teacher attitudes. Subscales of Focus on Others, Problems With Acceleration, Grade Skipping, Identification, and Curriculum/Policy and ranking the goals of gifted programming allow precise understanding of teacher attitudes reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
14

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 53 publications
(87 reference statements)
0
15
0
14
Order By: Relevance
“…In Croatia, teachers had a positive attitude toward the needs, support and social value of gifted education; on the other hand, they were slightly negative about the special provisions for the gifted (Perković Krijan et al, 2015). Also, a standardized questionnaire was developed to examine teachers' attitudes toward gifted education (Szymanski et al, 2018). The emerging factors on the questionnaire were the focus on others, grade skipping, acceleration concerns, identification and curriculum policy.…”
Section: Teachers' Attitudes Toward Gifted Educationmentioning
confidence: 99%
“…In Croatia, teachers had a positive attitude toward the needs, support and social value of gifted education; on the other hand, they were slightly negative about the special provisions for the gifted (Perković Krijan et al, 2015). Also, a standardized questionnaire was developed to examine teachers' attitudes toward gifted education (Szymanski et al, 2018). The emerging factors on the questionnaire were the focus on others, grade skipping, acceleration concerns, identification and curriculum policy.…”
Section: Teachers' Attitudes Toward Gifted Educationmentioning
confidence: 99%
“…Educator perceptions are vital to providing the opportunity for successful identification of all student groups. Szymanski et al (2018) created the Determining Attitudes Toward Ability (DATA) instrument as a systematic way to understand teachers' attitudes and views regarding the goals of gifted programming. The authors found that teacher experience with gifted students had the largest influence on their attitudes and understanding, regardless of education level, and teaching experience.…”
Section: Teacher Perceptionmentioning
confidence: 99%
“…Stališča učiteljev do nadarjenih in njihovega izobraževanja so eden ključnih dejavnikov kakovostnega pedagoškega dela učiteljev z nadarjenimi učenci v šoli (Szymanski et al, 2018). Univerzitetno okolje, v katerem se izobražujejo prihodnji učitelji, zato predstavlja temeljni kontekst, v katerem lahko učitelji usvojijo znanje in izkušnje, ki prispevajo k razvoju strokovnega, na empiričnih dokazih temelječega pedagoškega pristopa.…”
Section: Problem In Cilj Raziskaveunclassified
“…Predstavljeni rezultati so del širše raziskave, ki je potekala v okviru Centra za razvijanje in spodbujanje nadarjenosti (CRSN) (Pajares, 1992). Szymanski et al (2018) podarjajo, da imajo učitelji s svojimi stališči in vedenji med vsemi učenci največji vpliv na nadarjene, saj so oni najpogosteje tisti, ki jih prepoznajo za nadarjene in zanje predlagajo določene prilagoditve. Pozitivna stališča učiteljev ne vplivajo le na poučevalno prakso, ampak posredno tudi na stališča in vedenja sošolcev (vrstnikov) nadarjenih ter spodbudno razredno klimo, ki zagotavlja optimalen razvoj nadarjenih učencev (Al Makhalid, 2012).…”
unclassified